Utilization of Local Wisdom as a Learning Source in Designing Learning Tools: Culturally Responsive Teaching Negeri Hila - Limba, Anatasija; Sapulete, Heppy; Malawau, Seska; Batlolona, John Rafafy (Unram Journal of Community Service, 2024)
Community Service (PkM) activities were carried out by providing training to teachers at SMA Negeri 6 Maluku Tengah in Waitomu Hamlet-Negeri Hila. This activity aims to provide insight into the development of teacher professionalism, more specifically how deep the application of CRT in learning activities at school. This activity is expected to encourage teachers to improve their competence and motivation to become professional teachers. The activity was carried out in a structured and systematic manner in the form of providing in-depth material for teachers. The result of the community service is that subject teachers can develop learning tools based on local wisdom, namely CRT, which utilizes the surrounding environment as a learning resource. In addition, 100% of teachers like this activity, this is because there are many training activities both from the center and local governments, but CRT-based training activities are rarely delivered and are even new to teachers. The school hopes that lecturers can continue to provide assistance and training for teachers at SMA Negeri 6 Maluku Tengah by sharing new things so that they can apply them in learning. By embracing CRT in learning, it can create an inclusive, interesting, and empowering learning experience that meets the various needs of all students and helps close the gap in learning